Postnatal depression among Libyan women in Derna - Arhaiam, Fawzia A. G.; Ajroud, Soad; Elzahaf, Raga A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postnatal depression during postnatal period is a recurrence of pre-existing situation and one of the common types of mental health illness. Objectives were to explore the factors and prevalence of postnatal depression that influences on the women’s during postnatal period in Denra city and it surrounded suburbs. Methods: Design A prospective study was carried out and survey of practice. We used Edinburgh postnatal depression scale (EPDS) to collect data between January 2021 to December 2021 in Derna city and its suburbs. Participances women who took part in the study, met specific criteria such as their baby being born within the previous twelve months. Results: Overall, 100 women were included in this study. The mean age of women was 32.51±5.72 from 23 to 45 years. More than one third 36% of women were from Derna and 66% of women live in their own house. According to EPDS, found 47% of women were possible to expose to depression, 51% of women were complain from postnatal depression and 2% were attempted to suicide. The women delivered by caesarean section were at high risk of postnatal depression (p=0.001). Conclusions: Untreated postnatal depression led to harmful effect on the relationship between mother and her baby, her partner and other family members. lead to negative impact on society screening and early diagnosis for postpartum depression is important, essential and a vital role for health care professionals such as (midwives, health visitors, nurses and GPs).